Productivity and quality aspects concerning the laboratory rearing of Trichogramma spp. (Hym.: Trichogrammatidae) and its factitious host, Ephestia kuehniella Zeller (Lep.: Pyralidae) - Goncalves, C.I.=700 1 Amaro, F.; Figueiredo, E.; Godinho, M.C.; Mexia, A.
(Es, En)
ilus., 30 ref.
Keywords: TRICOGRAMMMA; EPHESTIA KUEHNIELLA; HUESPEDES; PRODUCTIVIDAD; CALIDAD; ESPAÑA; CRIA EN LABORATORIO